Disability-adjusted life years and mortality rate attributed to unsafe sex and drug use for AIDS in the Middle East and North Africa countries - Farid Najafi; Fatemeh Khosravi; Mojtaba Ghalandari; Mitra Darbandi (BMC, 2020)
Abstract Background The Middle East and North Africa, is one of few regions where the number of new human immunodeficiency virus infections is increasing. The present study aimed to estimate the attributable burden of unsafe sex and drug use in Acquired immunodeficiency syndrome in the Middle East and North Africa countries. Methods We used the Global Burden of Disease data 2017 to estimate the attributable mortality and disability-adjusted life-years to unsafe sex and drug use in Acquired immunodeficiency syndrome in the Middle East and North Africa countries (21 countries) from 1990 to 2017 by region, sex and age. The percent change was calculated at three time points by country and sex. Results The rate of Disability-adjusted life years/100,000 attributed to drug use for Acquired immunodeficiency syndrome increased 1.10 (95% CI: 0.75-1.71) to 13.39 (95% CI: 9.98-18.17) in women of Middle East and North Africa countries from 1990 to 2017, and there is an increasing trend in Disability-adjusted life years attributable to drug use for Acquired immunodeficiency syndrome in men. The rate of Disability-adjusted life years/100,000 attributed to unsafe sex for Acquired immunodeficiency syndrome increased in women of Middle East and North Africa countries, 5.15 (95% CI: 3.34-8.07) to 53.44 (95% CI: 38.79-75.89); and 10.06 (95% CI: 6.61-16.18) to 46.16 (95% CI: 31.30-72.66) in men. Age-standardized mortality rate attributed to drug use and unsafe sex for Acquired immunodeficiency syndrome increased from 1990 to 2017 in both sex in Middle East and North Africa countries. Conclusion The rate of Disability-adjusted life years /100,000 and age-standardized mortality rate attributed to unsafe sex and drug use increased in Middle East and North Africa from 1990 to 2017. While most of such countries have traditional cultures with religious believes, such increase need to be addressed in more depth by all policy makers.